Flash dietary methionine supply over growth requirements in pigs: Multi-facetted effects on skeletal muscle metabolism - F. Gondret; N. Le Floc'h; D.I. Batonon-Alavo; M-H. Perruchot; Y. Mercier; B. Lebret (Animal, 2021)
Dietary methionine affects protein metabolism, lean gain and growth performance and acts in the control of oxidative stress. When supplied in large excess relative to growth requirements in diets for pigs, positive effects on pork quality traits have been recently reported. This study aimed to decipher the molecular and biochemical mechanisms affected by a dietary methionine supply above growth requirements in the loin muscle of finishing pigs. During the last 14 days before slaughter, crossbred female pigs (n = 15 pigs/diet) were fed a diet supplemented with hydroxy-methionine (Met5; 1.1% of methionine) or not (CONT, 0.22% of methionine). Blood was sampled at slaughter to assess key metabolites. At the same time, free amino acid concentrations and expression or activity levels of genes involved in protein or energy metabolism were measured in the longissimus lumborum muscle (LM). The Met5 pigs exhibited a greater activity of creatine kinase in plasma when compared with CONT pigs. The concentrations of free methionine, alpha-aminobutyric acid, anserine, 3-methyl-histidine, lysine, and proline were greater in the LM of Met5 pigs than in CONT pigs. Expression levels of genes involved in protein synthesis, protein breakdown or autophagy were only scarcely affected by the diet. Among ubiquitin ligases, MURF1, a gene known to target creatine kinase and muscle contractile proteins, and OTUD1 coding for a deubiquitinase protease, were up-regulated in the LM of Met5 pigs. A lower activity of citrate synthase, a reduced expression level of ME1 acting in lipogenesis but a higher expression of PPARD regulating energy metabolism, were also observed in the LM of Met5 pigs compared with CONT pigs. Principal component analysis revealed that expression levels of many studied genes involved in protein and energy metabolism were correlated with meat quality traits across dietary treatments, suggesting that subtle modifications in expression of those genes had cumulative effects on the regulation of processes leading to the muscle transformation into meat. In conclusion, dietary methionine supplementation beyond nutritional requirements in pigs during the last days before slaughter modified the free amino acid profile in muscle and its redox capacities, and slightly affected molecular pathways related to protein breakdown and energy metabolism. These modifications were associated with benefits on pork quality traits.